Hippo and rassf1a Pathways: A Growing Affair. (5th July 2012) - Fausti, Francesca; Di Agostino, Silvia; Sacconi, Andrea; Strano, Sabrina; Blandino, Giovanni
Abstract : First discovered in Drosophila, the Hippo pathway regulates the size and shape of organ development. Its discovery and study have helped to address longstanding questions in developmental biology. Central to this pathway is a kinase cascade leading from the tumor suppressor Hippo (Mst1 and Mst2 in mammals) to the Yki protein (YAP and TAZ in mammals), a transcriptional coactivator of target genes involved in cell proliferation, survival, and apoptosis. A dysfunction of the Hippo pathway activity is frequently detected in human cancers. Recent studies have highlighted that the Hippo pathway may play an important role in tissue homoeostasis through the regulation of stem cells, cell differentiation, and tissue regeneration. Recently, the impact of RASSF proteins on Hippo signaling potentiating its proapoptotic activity has been addressed, thus, providing further evidence for Hippo's key role in mammalian tumorigenesis as well as other important diseases.